Synthesis of Asparagusic Acid Modified Lysine and its Application in Solid-Phase Synthesis of Peptides with Enhanced Cellular Uptake - Tirla, Alina; Hansen, Moritz; Rivera-Fuentes, Pablo (Synlett, 2018)
Cyclic disulfides, such as asparagusic acid, enhance the uptake of a variety of cargoes into live cells. Here, we report a robust and scalable synthesis of an asparagusic acid modified lysine. This amino acid can be used in solid-phase peptide synthesis. We confirmed that incorporation of this building block into the sequence of a peptide increases its cellular uptake substantially.
Keywords: asparagusic acid; modified amino acid; cellular uptake; solid-phase peptide synthesis; cell-penetrating peptides